Effects of NH4+ concentration on growth, morphology and NH4+ uptake kinetics of Salvinia natans - Jampeetong A. (2014)
Many plants develop toxicity symptoms and have reduced growth rates when supplied with ammonium (NH4+) as the only source of inorganic nitrogen. In the present study, the growth, morphology, NH4+ uptake kinetics and mineral concentrations in the tissues of the free-floating aquatic plant Salvinia natans (water fern) supplied exclusively with NH4+-N at concentrations of 0.25-15 mM were investigated. S. natans grew well, with relative growth rates of c. 0.25 g g-1 d-1 at external NH4+ concentrations up to 5 mM, but at higher levels growth was suppressed and the plants had small leaves and short roots with stunted growth. The high-affinity transport system (HATS) that mediate NH4+ uptake at dilute NH4+ levels was downregulated at high NH4+ concentrations with lower velocities of maximum uptake (Vmax) and higher half-saturation constants (K1/2). High NH4+ levels also barely affected the concentrations of mineral cations and anions in the plant tissue. It is concluded that S. natans can be characterized as NH4+-tolerant in line with a number of other species of wetland plants as growth was unaffected at NH4+ concentrations as high as 5 mM and as symptoms of toxicity at higher concentrations were relatively mild. Depolarization of the plasma membrane to the equilibrium potential for NH4+ at high external concentrations may be a mechanism used by the plant to avoid excessive futile transmembrane cycling. S. natans is tolerant to the high NH4+ levels that prevail in domestic and agricultural wastewaters, and the inherent high growth rate and the ease of biomass harvesting make S. natans a primary candidate for use in constructed wetland systems for the treatment of various types of nitrogen-rich wastewaters. © 2008 Elsevier B.V. All rights reserved.